If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X * 2 + 2x + -15 = 0 Reorder the terms for easier multiplication: 2X + 2x + -15 = 0 Reorder the terms: -15 + 2X + 2x = 0 Solving -15 + 2X + 2x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 2X + 15 + 2x = 0 + 15 Reorder the terms: -15 + 15 + 2X + 2x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 2X + 2x = 0 + 15 2X + 2x = 0 + 15 Combine like terms: 0 + 15 = 15 2X + 2x = 15 Add '-2x' to each side of the equation. 2X + 2x + -2x = 15 + -2x Combine like terms: 2x + -2x = 0 2X + 0 = 15 + -2x 2X = 15 + -2x Divide each side by '2'. X = 7.5 + -1x Simplifying X = 7.5 + -1x
| 3x^2-4=12 | | 1y+2=8 | | 72-5x=5x+9 | | v-9=7 | | x=15-1.25y | | x=15-1 | | m-(-3)=10 | | 1x+9=13 | | g+(-7)=9 | | 5x+10=6x-5 | | -25=q-15 | | 0=x+x^2 | | X+0.5x=60 | | 1x+10=6x-5 | | 5x+17=12x-60 | | 2x=48 | | 9y+7=52 | | -3x+7y+1=0 | | 1x+4=11 | | 0=4x-x^3 | | 11x-18=6x-2 | | 5x-16y+1=0 | | 6b^2+11b+3=0 | | 6x^2-12x-24=0 | | 1y+7=16 | | 6y+5=47 | | 6x^4+8x^3-8x^2=0 | | 7n-n=-48 | | 12-a=7 | | 12a=7 | | 5.1=1.02 | | (7x+3)(5x+9)=360 |